Analysis of direct medical costs in the inpatient treatment of sepsis at Thong Nhat Dong Nai General Hospital in 2024 - Vu, Nguyen Long; Son, Pham Luong; Cuc, Pham Thi; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Sepsis is a severe, life-threatening condition that imposes a substantial economic burden on both patients and the healthcare system. At Thong Nhat Dong Nai General Hospital, no prior study has evaluated the direct medical costs (DMCs) associated with inpatient treatment of sepsis. Objectives: To analyze the DMCs and identify factors associated with the inpatient treatment among sepsis patients at Thong Nhat Dong Nai General Hospital, in 2024. Methods: A cross-sectional descriptive study was conducted using a retrospective review of electronic billing data from sepsis inpatients who met the inclusion criteria at Thong Nhat Dong Nai General Hospital in 2024. Results: A total of 1,270 treatment episodes were analyzed. The mean patient age was 62.76 ± 16.91 years, with an average hospital stay of 11.91 ± 8.20 days. Most patients (95%) received broad-spectrum antibiotics. The mean DMC per inpatient sepsis episode was 13,440,089 VND (95% CI: 12,332,970 - 14,547,219 VND). Drug costs accounted for the largest proportion (41.51%) of total expenses, and health insurance covered 86.57% of total DMCs. The multivariable regression model demonstrated significant associations between log-transformed DMCs (adjusted R² = 0.661; p < 0.05) and the following predictors: Log(DMC) = 0.656 × “Length of stay” + 0.166 × “ICU admission” + 0.126 × “Other interventions” + 0.100 × “COPD/chronic lung disease” + 0.096 × “Chronic liver disease” + 0.079 × “Mortality” + 0.070 × “Diabetes mellitus” + 0.070 × “Broad-spectrum antibiotic use” + 0.062 × “Age” + 0.047 × “Chronic kidney disease” + 0.042 × “Surgery” + 6.159. Conclusions: The mean DMC per sepsis hospitalization was substantial, approximately one-fifth of Vietnam's estimated average per capita income in 2024. Drug costs represented the largest proportion of expenditures, while health insurance covered the majority of expenses. The multivariable regression identified eleven significant factors associated with DMCs (adjusted R² = 0.661).